봄철 서울 도로변의 검댕 오염 특성 - 이승복; 배귀남; 박수미; 정상근 (한국대기환경학회, 2007)
To understand particle pollution phenomena caused by vehicles, black carbon(BC) concentrations were contin-uously monitored using an aethalometer at a roadside in Seoul during the period of May 19 to 25, 2005. The BCBC concentration was observed between 2 and 5 a.m. The local highest BC concentrations were observed duringthe periods of both morning and evening rush hours. Change in trafc volume accounts for the trend of hourlyaveraged BC concentrations from the late evening to the morning. Particularly, the slower increase of BC concen-tration on Sunday seems to respond directly the lower trafc volume in the morning rush hours. From the compari-the distance from a road.